The Role Of Islam In Accounting - Robby Rahadi Putra; Rima Novita Sari (Proceeding International Seminar of Islamic Studies, 2019)
This paper aims to explain of idea the role of Islam in accounting. Every action taken must be by Islamic law and principles. Ethical principles define what is right, responsibility, and fairness. Based on the ethical principles in Islam, accounting requires fairness and honesty in corporate responsibility, which refers to accountability or transparency. The result of this paper indicates Islamic accounting is not about values but belief. This belief based on spiritual values learned from scripture and conscience.